COMMUNITY-BASED STUDY ON PREVALENCE AND PATTERN OF SELF-MEDICATION PRACTICES AND ITS ASSOCIATED FACTORS IN S.S LAYOUT, DAVANGERE - FATHIMA, NAZISH; JACOB, ANITTA MARIAM; VARUGHESE, ANJU; ABRAHAM, ARPITHA; MATHEW, ASHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Self-medication practice is an element of self-care and it is the use of medication without the prescription of health-care professionals. This community-based prospective observational study was undertaken with the aim to evaluate the prevalence and pattern of self-medication practices and to assess the knowledge, attitude, and belief of the subjects toward this practice. Methods: This study was carried out in S.S Layout, Davangere, for a period of 6 months. The data were collected in predesigned validated questionnaire. A total of 400 subjects were participated in the study. Results: Among 400 individuals, 280 subjects were practicing self-medication, and this practices were high among females 174 (62%) than males 106 (38%). The majority of subjects participated in this study were students (36%). The most common indications for self-medication practice were headache (30%) followed by fever (25%) and heartburn (13%). The highly used drug in this practice was acetaminophen (57%). The most commonly used category of drugs for self-medication were analgesics (57%) followed by antacids (17%) and others (anti-hypertensive, anti-diarrheal, anti-pyretic, anti-histamines, and laxative) (13%). The main reasons for self-medication practice were no need to visit the doctor for minor illness (62%), long distance to health center (24%), and inability to pay for health-care cost (6%). Conclusion: This study shows that self-medication is widely practiced among students in our society. There is dire need to make them aware about the pros and cons of self-medication in order to ensure safe usage of drugs. Interventions are required to reduce the frequency of misuse of drugs.